Analyzing the Implementation of Internet of Things to Enhance Service Quality at Bobocabin The Tavia, Bogor - Liora, Fernanda; Susanto, Prayogo (Gema Wiralodra, 2025)
Bobocabin The Tavia is a glamping accommodation that combines the concept of staying in nature with Internet of Things (IoT) based technology. Using a qualitative approach with a phenomenological method, this study explores how the implementation of Internet of Things systems supports service quality improvement from the perspective of guests and operational staff. Data collection techniques include in-depth interviews, direct observation, and documentation.The results of the study indicate that the six main dimensions of the Internet of Things such as connectivity, interactivity, comfort, security, intelligence, and telepresence contribute significantly to the five dimensions of service quality based on the SERVQUAL model, namely reliability, tangibles, responsiveness, assurance, and empathy. Features such as smart lamps, smart glass, B-pad, and QR code door locks allow guests to independently and in real-time control their cabin environment. However, some technical challenges remain, such as delayed responses from smart lamps and connectivity issues. This study offers practical insights for accommodation providers, particularly in technology-based glamping services, to support digital tourism. Additionally, the findings serve as an academic reference for future research on IoT integration in enhancing service quality in the tourism sector.